Assessment of some leucocytic enzymes in relation to etiopathogenesis of retention of fetal membranes in crossbred cows - Gupta, Sandeep Kumar; Kumar, Harendra; More, T (The Indian Journal of Animal Sciences, 2011)
The certain cationic peptides including myeloperoxidase (MPO), lysozyme, elastase and acid phosphatase (ACP) were analyzed in the cotyledons collected from cows with or without retention offetal membranes (RFM). A significantly lower (O.73±O.06 vs I.18±0.08,P